Portrayal and the search for identity - Pointon, Marcia R. (Reaktion, 2013)
We are surrounded with portraits: from the cipher-like portrait of a president on a bank note to security pass photos; from images of politicians in the media to Facebook; from galleries exhibiting Titian or Leonardo to contemporary art deploying the self-image, as with Jeff Koons or Cindy Sherman. In antiquity portraiture was of major importance in the exercise of power. Today it remains not only a part of everyday life, but also a crucial way for artists to define themselves in relation to their environment and their contemporaries. In Portrayal and the Search.